Quality metrics in solid organ transplantation: protocol for a systematic scoping review. Issue 1 (December 2016) - Brett, Kendra; Bennett, Alexandria; Fergusson, Nicholas; Knoll, Greg
Abstract Background Transplantation is often the best, if not the only treatment for end-stage organ failure; however, the quality metrics for determining whether a transplant program is delivering safe, high quality care remains unknown. The purpose of this study is to identify and describe quality indicators or metrics in patients who have received a solid organ transplant. Methods/design We will conduct a systematic scoping review to evaluate and describe quality indicators or metrics in patients who have received a solid organ transplant. We will search MEDLINE, Embase, and the Cochrane Central Register for Controlled Trials. Two reviewers will conduct all screening and data extraction independently. The articles will be categorized according to the six domains of quality, and the metrics will be appraised using criteria for a good quality measure. Discussion The results of this review will guide the development, selection, and validation of appropriate quality metrics necessary to drive quality improvement in transplantation. Systematic review registration PROSPEROCRD42016035353 .